Trees of the Central Valley of Costa Rica: reproduction Guachipelín (Diphysa americana (Mill.) M. Sousa) - Rojas-Rodríguez, Freddy (2018)
The following issue presents a brief description about the “Guachipelín” tree (Diphysa americana (Mill.) M. Sous), including information about its phenology which directly relates to fruit recollection, seed treatment, nursery, and germination processes.